2013
DOI: 10.1115/1.4025996
|View full text |Cite
|
Sign up to set email alerts
|

The Power and Efficiency Limits of Piezoelectric Energy Harvesting

Abstract: The fundamental limits of cantilevered piezoelectric energy harvesters have not been well established. As with any other power generation technology, it is critical to establish the limits of power output and efficiency. Mathematical models for piezoelectric energy harvester power output have seen continued refinement, but these models have mainly been used and compared to individual harvester designs. Moreover, existing models all assume power scales with acceleration input, and take no account for the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Field-induced strain (S-E) curves were measured using a laser displacement sensor (LK-G10, Keyence Co. Tokyo, Japan) with a resolution of 10 nm and a spot size of 20 lm. Figure 1 shows the XRD patterns of the PZ 1Àx T x -PZNN (0.50 ≤ x ≤ 0.55) ceramics sintered at 1150°C for 2 h. The inset shows the (111) peak of the specimen with x = 0.52 obtained by slow scanning; the (111) peak consisted of two peaks, (111) and (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), indicating that this specimen had a rhombohedral structure. Therefore, it was concluded that the specimens with x ≤ 0.52 had a rhombohedral structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field-induced strain (S-E) curves were measured using a laser displacement sensor (LK-G10, Keyence Co. Tokyo, Japan) with a resolution of 10 nm and a spot size of 20 lm. Figure 1 shows the XRD patterns of the PZ 1Àx T x -PZNN (0.50 ≤ x ≤ 0.55) ceramics sintered at 1150°C for 2 h. The inset shows the (111) peak of the specimen with x = 0.52 obtained by slow scanning; the (111) peak consisted of two peaks, (111) and (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), indicating that this specimen had a rhombohedral structure. Therefore, it was concluded that the specimens with x ≤ 0.52 had a rhombohedral structure.…”
Section: Methodsmentioning
confidence: 99%
“…2 Piezoelectric energy harvesters, which convert the wasted energy from mechanical vibrations into usable electrical energy, have been extensively investigated for use as power sources in wireless devices and various sensors. [3][4][5][6][7][8][9][10][11] Piezoelectric ceramics used in such devices should be capable of generating a considerable amount of electrical energy even for a small input vibration. The electrical energy density (u) produced by piezoelectric ceramics is generally expressed by the following equation: u = (1/2)(d ij 9g ij )(F/A), 12 where d ij is the piezoelectric strain constant; g ij is the piezoelectric voltage constant; F is the applied force; and A is the area of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The formula derived by Yang et al [15] was found to be exactly the same as the one introduced by Kim et al [14]. Shafer and Garcia [16] derived an expression for the average efficiency at the steady state by dividing the average harvested energy by the average change in the energy state of the system (heat losses + energy lost in damping + harvested energy). They reported that for the conservative case (heat losses = 0), their formula would be the same as the one proposed by Shu and Lien [13].…”
Section: Expressions For Estimating Efficiencymentioning
confidence: 85%
“…The output power of the vibration energy harvester is dependent on many factors and varies if the operation is on resonance or off resonance. Yang et al [15] Efficiency η 4 η 4 = rQk 2 1+k 2 rQ+ ω 2 r 2 Shafer and Garcia [16] Average efficiency η av…”
Section: Expressions For Estimating Efficiencymentioning
confidence: 99%
“…The main limitations of piezoelectric energy harvesting are low efficiency and power output. This is large concern with biomedical devices, because they often do not operate at the device's resonance frequency [115]. Another avenue of research focuses on enhancing the efficiency of energy harvesting by mechanically scraping screening charges found on the surface of piezoelectric materials [116][117][118][119].…”
Section: Energy Harvestingmentioning
confidence: 99%